Enhancement of Squeezing and Entanglement in a Non-Degenerate Three-Level Cascade Laser with Coherently Driven Cavity - Abebe, T. (Ukrainian Journal of Physics, 2018)
We study a nondegenerate three-level cascade laser coupled to a two-mode vacuum reservoir, by employing the stochastic differential equations associated with the normal ordering. The amplification of the properties of squeezing and entanglement of the cavity light is investigated. We have found that there is an entanglement between the states of the light generated in the cavity, due to the strong correlation of the light emitted, when the atom decays from the top level to the bottom level via the intermediate one. We have also obtained that the two cavity modes are strongly entangled, and the degree of entanglement is directly related to the two-mode squeezing.